2021
DOI: 10.3390/insects12010045
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Spatiotemporal Variation of Longhorn Beetles (Coleoptera: Cerambycidae) in Tropical Forest of Thailand

Abstract: Longhorn beetles are highly diversified and important for agriculture and health of the environment. However, the fauna and ecology of these beetles are not well known in Thailand. This study is the first to report the biodiversity, elevation, and seasonal distribution of longhorn beetles. Specimens were collected by malaise traps from 41 localities in 24 national parks throughout the country during 2006–2009. The traps were operated at each site for 12 consecutive months with a monthly service. A total of 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The spatial distribution of insects has been reported in various insect groups, and the results revealed different relationships depending on the taxa [ 23 , 29 , 30 , 64 , 65 , 66 , 67 ]. Our result showed a hump-shaped distribution pattern of this insect, which was similar to previous reports from the Qinling mountains in Yunan province and the Sichuan Basin in Sichuan province, China, suggesting that the highest species numbers occurred in the middle elevation [ 22 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of insects has been reported in various insect groups, and the results revealed different relationships depending on the taxa [ 23 , 29 , 30 , 64 , 65 , 66 , 67 ]. Our result showed a hump-shaped distribution pattern of this insect, which was similar to previous reports from the Qinling mountains in Yunan province and the Sichuan Basin in Sichuan province, China, suggesting that the highest species numbers occurred in the middle elevation [ 22 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This placement endows Thailand with rich biodiversity, particularly in its flora and fauna [ 27 ]. Insects are especially diverse, with over 10,000 species recorded [ 28 ], and numerous studies have reported on insect diversity, distribution, and community structure within the country [ 29 , 30 , 31 , 32 , 33 ]. In the case of Mecoptera, there has been a significant increase in the number of species identified in Thailand over the past five years.…”
Section: Introductionmentioning
confidence: 99%
“…Diversity patterns of phytophagous beetles are known to be generally linked to species turnover of their host plants (Kemp et al, 2017; Luo et al, 2021; Ødegaard, 2006) and their distribution is correlated with the region and forest type (Yotkham et al, 2021). Other guilds, such as dung‐feeding beetles, respond to shade cover rather than plant species composition.…”
Section: Introductionmentioning
confidence: 99%
“…Diversity patterns of phytophagous beetles are known to be generally linked to species turnover of their host plants (Ødegaard 2006;Kemp et al 2017;Luo et al 2021) and their distribution is correlated with the region and forest type (Yotkham et al 2021). Other guilds, such as dung feeding beetles, respond to shade cover rather than plant species composition.…”
Section: Introductionmentioning
confidence: 99%